Clinical Study Reports—a systematic review with thematic synthesis: Part 2. Studying benefits, harms, and the benefit to harm balance of pharmacological interventions - J. K. Aronson; I. J. Onakpoya (Trials)
Abstract Background We define clinical study reports (CSRs) as standardized full reports of the protocols, results, and other pertinent details of clinical studies that are typically submitted by pharmaceutical companies to regulatory authorities when they apply for marketing authorization. Methods In this systematic review we searched various databases (Clarivate Web of Science, EMBASE and Ovid Medline, Google Scholar, and PubMed) for publications containing the term “clinical study report/s”, without restrictions. Thematic synthesis In the first part of this review we discussed the history of CSRs, their contents and structure, definitions, and relevant terminology. In this second part we discuss the uses of CSRs, concentrating on the individual benefits and harms of pharmacological interventions, and thus the benefit to harm balance. We also discuss adherence to interventions, prepublication of protocols of clinical trials, and how CSRs are written, factors that can all affect estimation of the benefit-harm balance. Conclusions When clinical trial data from CSRs are compared with the data in published trial reports, the apparent benefits of pharmacological interventions are less impressive, and more information emerges about harms they can cause. Both of these effects change how the benefit-harm balance of a pharmacological intervention is estimated, generally making it less favourable than was otherwise thought. For more accurate assessment of the benefit-harm balance of an intervention, full, not abbreviated or synoptic, clinical study reports should continue to be made publicly available by regulatory authorities and manufacturers. Authorities that do not currently make them available should do so. CSRs should be introduced for assessment of surgical operations, therapeutic devices, and other non-pharmacological interventions in clinical trials.